JWST-TST DREAMS: A Precise Water Abundance for Hot Jupiter WASP-17b from the NIRISS SOSS Transmission Spectrum - Dana R. Louie; Elijah Mullens; Lili Alderson; Ana Glidden; Nikole K. Lewis; Hannah R. Wakeford; Natasha E. Batalha; Knicole D. Colón; Amélie Gressier; Douglas Long; Michael Radica; Néstor Espinoza; et al. (The Astronomical Journal)
Water has proven to be ubiquitously detected in near-infrared (NIR) transmission spectroscopy observations of hot Jupiter atmospheres, including WASP-17b. However, previous analyses of WASP-17b’s atmosphere based upon Hubble Space Telescope (HST) and Spitzer data could not constrain the water abundance, finding that subsolar, supersolar, and bimodal posterior distributions were all statistically valid. In this work, we observe one transit of the hot Jupiter WASP-17b using JWST’s Near Infrared Imager and Slitless Spectrograph (NIRISS) Single Object Slitless Spectroscopy (SOSS) mode. We analyze our data using three independent data analysis pipelines, finding excellent agreement between results. Our transmission spectrum shows multiple H _2 O absorption features and a flatter slope towards the optical than seen in previous HST observations. We analyze our spectrum using both PICASO + Virga forward models and free retrievals. POSEIDON retrievals provide a well-constrained supersolar log(H _2 O) abundance (−2.96 ${}_{-0.24}^{+0.31}$ ), breaking the degeneracy from the previous HST + Spitzer analysis. We verify our POSEIDON results with petitRADTRANS retrievals. Additionally, we constrain the abundance of log(H ^− ), −10.19 ${}_{-0.23}^{+0.30}$ , finding that our model including H ^− is preferred over our model without H ^− to 5.1 σ . Furthermore, we constrain the log(K) abundance (−8.07 ${}_{-0.52}^{+0.58}$ ) in WASP-17b’s atmosphere for the first time using space-based observations. Our abundance constraints demonstrate the power of NIRISS SOSS’s increased resolution, precision, and wavelength range to improve upon previous NIR space-based results. This work is part of a series of studies by our JWST Telescope Scientist Team (JWST-TST), in which we use Guaranteed Time Observations to perform Deep Reconnaissance of Exoplanet Atmospheres through Multi-instrument Spectroscopy (DREAMS).